Study of some morphological, morphological, productive and grazing characteristics of white clover cultivars (Trifolium repens L.) in three locations in Lattakia - حميشة ولاء; درويش مجد; محمد الخطيب (Latakia University Journal -Biological Sciences Series, 2022)
The research was carried out in three areas of Lattakia (Video, Bahloulia and Al-Mazira) in three replicates during the 2021 agricultural season. This research aimed to study the biodiversity and some forage characteristics of white clover cultivars, and their presence in open pastures. So, 30 plants were identified in each of the three sites that have different heights above sea level, and then the growth and development indicators were recorded until they reached the stage of flowering and maturity. A number of morphological (plant length cm, number of leaves/plant), morphysiological (leaf surface area cm2, leaf area index), biochemical (chlorophyll and carotenoids content µg/g FW, soluble sugars and proteins content %), productive (biomass for plant g/m2, dry plant weight g) and pasture characteristics (density of plant species plant/m2, optimal animal load for pasture/ha) for each cultivar on 10 samples in each of the three sites, where each plant is about a meter apart using the squares method, were measured. The white clover cultivar at Al-Mazira site were superior as compared to other sites in all morphological, morphological and productive characteristics, while the white clover at Al-Bahloulia site gave the highest values in terms of their biochemical composition, except for the content of total proteins, which was characterized by the white clover cultivars at Al-Mazira site, and the averages of studied traits fluctuated between the minimum and the highest within each site.